Influence of Ovsynch protocol on sexual behavior and fertility of ewes and ewe lambs (Research, Society and Development, 2022)
This study aimed to evaluate the sexual behavior and fertility of ewes and ewe lambs after the application of an estrous induction/synchronization protocol using GnRH. The females were randomly distributed in two experimental groups: group 1 (G1) was composed of pluriparous ewes aged 2 to 3 years, and group 2 (G2) was composed of ewe lambs, aged 7 to 8 months. All females were subjected to the Ovsynch protocol, which consisted of GnRH administration on day 0 (D0), d-cloprostenol seven days later (D7), and a second dose of GnRH (D9) was administered 48 hours later. Estrus observations were initiated immediately after PGF2α application, and were performed three times daily, lasting 4 days.  The animals of G2 did not manifest signs of estrus. Of the total treated females in G1, 85.7% showed signs of estrus. The pregnancy rate obtained in G1 animals was 83.3% (5/6), which was confirmed by a positive pregnancy diagnosis at 40 days post-coverage. In conclusion, the results showed that the hormonal treatment Ovsynch was efficient in inducing/synchronizing estrus, as well as producing high pregnancy rate in pluriparous ewes. However, the same protocol was not efficient in young animals (ewe lambs).